A two-step model to optimise transcutaneous electrical stimulation of the human upper arm. Issue 4 (1st July 2014) - Goffredo, Michela; Schmid, Maurizio; Conforto, Silvia; Bilotti, Filiberto; Palma, Claudio; Vegni, Lucio; D'Alessio, Tommaso
Abstract : Purpose: – A novel model of the upper arm under transcutaneous electrical stimulation with multi-pad electrodes is presented and experimentally validated. The model aims at simulating and analysing the effects of surface electrical stimulation on biceps brachii. The paper aims to discuss these issues. Design/methodology/approach: – Both the passive properties of tissues surrounding nerve bundles and the active characteristics of the nervous system are included. The output of the proposed model is nerve recruitment and muscle contraction. Findings: – Simulations and experimental tests on six healthy young adults have been conducted and results show that the proposed model gives information on electrically elicited muscle contraction in accordance with in-vivo tests and literature on motor unit recruitment order. Tests with different electrodes configurations show that the spatial distribution of active electrodes is a critical factor in electrically elicited muscle contractions, and that multi-pad electrodes can optimise the stimulation effectiveness and patient comfort with sequences of biphasic pulses of 350 μ s at 30 pulses/s and threshold values of 2 mA. Originality/value: – Results encourage the use of the proposed model of the upper arm as a valid and viable solution for predicting the behaviour of the neuromuscular system when surface electrical stimulation is applied, thus optimising the design of neuroprosthetics.